Pemberantasan Sarang Nyamuk (PSN) Sebagai Upaya Pencegahan Kasus Demam Berdarah Dengue (DBD) di Yogyakarta - Hikmah Nurul Avida; Salsabela Afra Ramadhani; Elrifa Luthfia Azzahra; Fikri Adriani; Delva Ine Dhewanti; Heru Subaris Kasjono; Bambang Suwerda (JPS : Jurnal Pengabdian Serulingmas, 2022)
Dengue fever (DHF) is caused by the dengue virus which spreads from person to person through the blood of the Aedes aegypti mosquito, it is important for people to do 3M, namely draining, closing and recycling can reduce dengue cases. DHF cases appear every year in the Onggobayan hamlet, one of which is the Sleman Regency hamlet. Our investigation carried out both from the Kasihan II health center, health cadres, the community and the head of the hamlet from the Onggobayan hamlet, it was found that the environment of several Neighborhood Associations (RT) in the Onggobayan hamlet was indeed unhealthy or could be considered slum.. The purpose of this program is to prevent dengue cases in 2022, through the Mosquito Nest Eradication (PSN) program in the Onggobayan hamlet with mature procedures. This research was conducted in January 2022. The design of this study was observational with a total sample of 40 samples consisting of 8 RT. In this activity program, it is divided into 3 stages, namely the implementation stage, the larva survey stage, and the implementation stage of the discussion results. The results of the activity obtained data that there were 10 residents' houses that were positive for mosquito larvae, besides that people generally drained the bathroom only once a week, and after the survey the residents would be given abate and antimosquito plants.